Oxidative Stress in Aging From Model Systems to Human Diseases - Miwa, Satomi; Beckman, Kenneth Bruce; Muller, Florian; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
Oxidative Stress in Aging: From Model Systems to Human Diseases discusses the role of free radicals in aging in different animal models, as well as the relevance of free radicals on age-related diseases and pathological conditions in humans (following an introduction section of the basics and theory of free radicals). Human aging is a complex phenomenon - not everyone gets the same diseases and dies from the same cause. Accumulating reports implicate the connection between free radicals and various diseases and age-related pathological conditions. Although the causal relationships have not been established, it is necessary to discuss how free radicals are involved in each situation. In addition, the major interventions trials of antioxidant supplements in age-related disease, cancer and so forth are reviewed and discussed.
The Basics of Oxidative Biochemistry -- The Role of Oxidative Stress in Aging -- Retrograde Response, Oxidative Stress, and Cellular Senescence -- Reactive Oxygen Species in Molecular Pathways Controlling Aging in the Filamentous Fungus Podospora anserina -- Oxidative Stress and Aging in the Budding Yeast Saccharomyces cerevisiae -- Oxidative Stress and Aging in the Nematode Caenorhabditis elegans -- Roles of Oxidative Stress in the Aging Process of Drosophila melanogaster -- Does Oxidative Stress Limit Mouse Life Span? -- Mitochondrial Free Radical Production and Caloric Restriction: Implications in Vertebrate Longevity and Aging -- Oxidative Stress in Human Aging and Diseases -- Deregulation of Mitochondrial Function: A Potential Common Theme for Cardiovascular Disease Development -- Oxidative Stress in Type 2 Diabetes Mellitus -- DNA Oxidative Damage and Cancer -- Oxidative Stress in Hypertension -- Aging and Cardiac Ischemia—Mitochondria and Free Radical Considerations -- Role of the Antioxidant Network in the Prevention of Age-Related Diseases -- Future -- Reactive Oxygen Species as Signaling Molecules -- Summary and Outlook.
Keywords: Geriatrics; Internal medicine; Cell biology; Geriatrics/Gerontology.; Internal Medicine; Cell Biology